Антология выдающихся достижений в науке и технике. Часть 25: Открытия в биологии и генетике живых организмов - Баранов, М.И. (Електротехніка і електромеханіка, 2015)
Приведен краткий очерк из всемирной истории основных достижений человечества в области биологии и генетики
различных живых организмов. Наведено короткий нарис з всесвітньої історії основних досягнень людства в області біології і генетики різних живих
організмів. Purpose. Formulation in the compressed type of basic scientifically-historical information, touching the topics for all of humanity and biological science − geneticists taking into account
the known for today scientific achievements on the way of its
evolutional development is presented. Methodology. Scientific
methods of receipt and systematization of knowledges. Methods
of historical method at becoming and development of biological
science and genetics. Results. Short history of origin and becoming of classic genetics is described. The portraits of row of
domestic and foreign scientists, bringing in a prominent contribution to development of genetics as sciences are presented.
Short general biological bases of heredity are given for living
organisms. Information is resulted about basic modern fundamental achievements and scientific openings of humanity in area
of biology and genetics of living organisms. Originality. First by
a scientist-electro-physicist for the wide circle of readers the
simple and clear appearance is expound short basic scientific
information about genes, genome and difficult mechanisms of
transmission in the animal (vegetable) kingdom of the inherited
information. Practical value. System built scientific popularization of existent knowledges of humanity in area of such section
of biological science as genetics and expansion for the large
number of people of scientific range of interests about outward
us things and flowings in its difficult biological processes.